Accounting for research and development costs and goodwill : issues and controversies - Chua, Bee Leng (2013)
As technology advances and firms globalise, intangible assets such as research and development costs and goodwill are fast becoming an important category in the financial statements. In the presence of much controversy over the accounting treatments for these two items in most countries, the project attempts to provide an insight into the arguments for and against each alternative treatment as well as a more in-depth understanding of accounting issues revolving round R&D costs and goodwill.